Mathematical Modelling and Numerical Simulation of Transmission Dynamics of COVID-19 Pandemic - SOME, Windjiré; LAMIEN, Kassiénou; SO, Ousséni; SOME, Blaise (International Journal of Applied Mathematical Research, 2022)
Â In this paper we have conceived an original deterministic model for the propagation of Covid-19 dynamics. Mathematical analysis of the model has been done and reveals the existence of a single disease-free equilibrium witch is locally and asymptotically stable. The basic reproduction number Â has also been evaluated and gives an idea on the disease evolution in the world. This is because if , the disease disappears whereas if , the disease remains in the population. Numerical results are consistent with the theoretical results and highlight the effect of the infectious contact rate Î± on the evolution of the pandemic.Â